Identifikasi Karakteristik Dan Pola Parkir Kendaraan di Bandar Udara Rendani: Identify Characteristics and Parking Patterns of Vehicles at Rendani Airport - Budi Prasetio; Indra Birawaputra; Yoga Charol Vincenthius Tethool (Universitas Papua, 2023)
The main air transportation hub for the city of Manokwari is Rendani Airport. The number of passengers and flights is currently increasing from year to year. Therefore, this study aims to determine the characteristics of car parking, especially at Rendani Airport. This study conducted a direct field survey by recording entry and exit tickets to collect vehicle data. The data collected shows that the highest parking volume is 131 vehicles, parking accumulation is 93 vehicles, parking lasts between one and fifteen minutes, the highest parking turnover rate is 0.873 vehicles/parking area, and the average parking index is 39.2. %. Whereas for two-wheeled vehicles, the highest parking turnover rate was 0.391 vehicles/parking area, the highest parking volume was 43 vehicles, the highest parking accumulation was 52 vehicles, and the average parking index was 34.0%. Vehicle parking duration ranges from one to fifteen minutes. This shows that the parking index is less than 100%, this shows that the vehicle parking at Rendani Airport can still accommodate requests determined from the results of calculating the characteristics of vehicle parking at Rendani Airport, the average car parking index is 39.2 percent. and 34.0% for motorcycles in 60 minute intervals. Director General of Land Transportation Standard No: 272/HK.105/DRJD/96 mentions Guidelines for Planning and Operation of Parking Facilities. On two-wheeled vehicles, the size and pattern meet the requirements. The angle and width of the vehicle compartment meet the requirements for four-wheeled vehicles, but the maneuverability space is not up to standard.